Homeopathic treatment as an alternative prophylactic to minimize bacterial infection and prevent neonatal diarrhea in calves - Fortuoso B.F.* (2018)
© 2017 Elsevier LtdBovine neonatal diarrhea is common due low immunity in newborn calves, poor management (or absence) of sanitary barriers, and other factors. Newborn calves with diarrhea in the first days of life suffer failure to thrive and may die if left untreated. The aim of this study was to evaluate whether prophylactic administration of a homeopathic product (Dia 100®) can control bovine neonatal diarrhea in calves born on a farm with substantial sanitary challenges. We counted total bacteria and protozoan parasites in fecal samples. We measured serum glucose, total protein, globulin, albumin, cholesterol and triglycerides on days 1, 7 and 14 of life. Twenty newborn calves were maintained in individual stalls, and were divided in two groups: ten untreated animals (control) and ten animals treated with Dia 100®. Fecal consistency was evaluated daily. We diagnosed diarrhea in five animals in the treated group, and in all animals from the control group. Infections with Escherichia coli and Giardia duodenalis were identified as the responsible organisms. The E. coli count was low in the treatment group on day 7 of life compared with the control group. Antibiotics were given to eight animals in the control group, and to two animals in the treatment group. On day of life 7, serum levels of total protein and globulins were higher in the control group, but were lower on day 14. Serum levels of glucose and triglycerides were greater in treated animals on days 7 and 14, suggesting that the homeopathic product contributes to improvement of intestinal health and absorption and nutrients. We conclude that Dia 100® controls diarrhea with 50% of efficacy, and reduces antibiotic utilization.